2016
DOI: 10.1109/tcomm.2016.2580153
|View full text |Cite
|
Sign up to set email alerts
|

Mode Selection, Resource Allocation, and Power Control for D2D-Enabled Two-Tier Cellular Network

Abstract: This paper proposes a centralized decision making framework at the macro base station (MBS) for device to device (D2D) communication underlaying a two-tier cellular network. We consider a D2D pair in the presence of an MBS and a femto access point, each serving a user, with quality of service constraints for all users. Our proposed solution encompasses mode selection (choosing between cellular or reuse or dedicated mode), resource allocation (in cellular and dedicated mode) and power control (in reuse mode) wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…Different from [26]- [31], which explored the mode selection and spectrum partition issues from the perspective of sum rate maximization, the authors in [32] investigated the optimal mode selection and spectrum partition to maximize the overall energy efficiency in a network with one base station, one CUE and one potential D2D pair. It is notable that this paper differs from the above works by jointly investigating the mode selection and spectrum partition issues from the PLS perspective.…”
Section: Related Workmentioning
confidence: 99%
“…Different from [26]- [31], which explored the mode selection and spectrum partition issues from the perspective of sum rate maximization, the authors in [32] investigated the optimal mode selection and spectrum partition to maximize the overall energy efficiency in a network with one base station, one CUE and one potential D2D pair. It is notable that this paper differs from the above works by jointly investigating the mode selection and spectrum partition issues from the PLS perspective.…”
Section: Related Workmentioning
confidence: 99%
“…In [20], PC and resource allocation schemes are considered; however, the interference between D2D pairs is ignored. In [21], a transmission cost minimization problem using hypergraph model is investigated based on a content encoding strategy to download a new content item or repair a lost content item in D2D-based distributed storage systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [22], [23], resource allocation is considered where one D2D link shares resources with only one cellular user in the underlay case. Obviously, these schemes in [20]- [23] are not spectrally efficient because D2D pairs are restricted to use different resource allocations. In [28], [29], power control is studied in random ad hoc networks without taking into consideration the underlaid cellular network.…”
Section: Introductionmentioning
confidence: 99%
“…Interference limited areas are defined to forbid sharing resources between D2D pairs and cellular users [12]. Besides, mode selection among overlay, underlay and cellular communications is another critical issue in D2D communications [22]- [26]. In [22], a communication mode was selected according to the distance between involved devices, where an optimal mode selection threshold that minimizes the transmit power was used.…”
mentioning
confidence: 99%
“…Dynamic mode selection on a slot-by-slot basis was proposed in [24], where it was shown that dynamic mode selection outperforms semi-static method. For D2D underlaying a two-tier cellular network, a centralized mode selection mechanism was proposed in [26]. When orthogonal resources are available, the D2D overlay mode is selected if D2D pairs are close to each other.…”
mentioning
confidence: 99%